2021
DOI: 10.1080/16089677.2021.1927586
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 deficiency in patients with diabetes at a specialised diabetes clinic, Botswana

Abstract: To estimate the prevalence of Vitamin B12 deficiency among patients with diabetes. Methodology: This cross-sectional study was undertaken on 351 patients with diabetes at a specialised public diabetes clinic in Gaborone between July 2017 and October 2017. Clinical, anthropometry and laboratory data were collected. Vitamin B12 deficiency was defined by levels < 150 pmol/l. Results: The mean (SD) age of the participants was 57 ( 15) years, two-thirds (67.2%) were females, and the majority (92.9%) had Type 2 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…The results of examining the gender variable of the patients showed that most of the studied patients were female, which is the same as the results of the study by Kwape et al (2021) in Botswana, where most of the studied patients were female (29). While in other studies, unlike the present study, most of the examined patients were male (30,31).…”
Section: Discussionsupporting
confidence: 88%
“…The results of examining the gender variable of the patients showed that most of the studied patients were female, which is the same as the results of the study by Kwape et al (2021) in Botswana, where most of the studied patients were female (29). While in other studies, unlike the present study, most of the examined patients were male (30,31).…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of B12 deficiency amongst people with diabetes across Southern Africa varies, ranging from 6.6% to 28.1%. (20,25) This observation is similar to that observed in high-income countries and could be a function of many factors. The disparity (almost double) in the prevalence of B12 deficiency between our cohort and that of Ahmed et al (28.1%) was an unexpected finding, given that both studies were conducted in tertiary hospitals in the same province of Gauteng.…”
Section: Prevalence Of B12 Deficiencysupporting
confidence: 86%
“…(20) The mean age in our study was 61.5 ± 12.1 years of age, similar to both the Botswana and South African studies, where the mean ages were 57 ± 15 and 58.5 ± 10.5 years, respectively. (20,25) In our study, B12-deficient patients were significantly older than those not B12-deficient. We noted the same trend in Ahmed and colleagues' report.…”
Section: Demographicsmentioning
confidence: 46%
See 2 more Smart Citations